Socioeconomic Status as a Root Cause of Child Malnutrition - Rosmita Nuzuliana; Ellyda Rizki Wijhati (Jurnal Kesehatan Masyarakat, 2025)
Nutritional problems increase the prevalence of brain disorders and intellectual devel- opment disorders in underweight toddlers by 52%, severe stunting by 6.32%, and severe wasting by 1.22%. The type of qualitative research is related to problems in toddlers who experience nutritional issues. The primary informants were 9 mothers who had malnourished toddlers. Data triangulation involved nutritionists, health cadres, and health center midwives. The research location was in the working area of the Bantul Regency Health Center, Special Region of Yogyakarta. Data were taken by in-depth interviews and home observations. The instruments used were interview guidelines and Healthy Home assessment instruments. Data analysis used thematic analysis. The results obtained 5 themes, including low socio-economic status, health status, parenting style and feeding of toddlers with permissive and unresponsive parenting styles, low maternal education, and poverty resulting in low provision of quality food. Almost all malnourished toddlers experience health problems, and unhealthy housing conditions, and nutrition management carried out by the health center is good.